Domestic Wastewater Treatment and Lipid Accumulation for Biodiesel Production by an Isolated Heterotrophic Microalgae from an Arid Climate Zone - El Asli, Abdelghani; El Mesbahi, Nadia; Oubakalla, Rachida; El Fels, Loubna; Hafidi, Mohamed; Liang, Yanna (The Asia Journal of Applied Microbiology, 2019)
The isolation of microalgae that can use carbon-rich pollutant from wastewater and accumulate lipids is of great interest in biodiesel production. The heterotrophic cultivation of microalgae could overcome light dependency, and hence increase the yield of microalgae lipid per unit area. After several microbial screening and acclimation procedures, strains of microalgae were proved to be tolerant of wastewater and to grow heterotrophically. One top-performing strain (AE2) was identified through morphological observation as Chlorella sp and was isolated from an open pond of domestic wastewater. This microalgae is able to grow in raw wastewater at 20°C with no illumination and eliminates 100% of its COD (424 mg/L) in 9 days. The biomass produced in wastewater as growth medium comprises 53% of fats of the dry mass and 68% of fats of the dry mass in BG 11 culture medium supplemented with 5 g of glucose/L. The analysis of fatty acid methyl esters FAME composition was 32.5 % of the total biomass. The extracted microalgae oil was converted to good quality biodiesel. This heterotrophic isolated microalgae is a promising strain in terms of wastewater COD removal and cytoplasmic accumulation of high quality and quantity lipids for prospective biodiesel production.